Combination therapy of modified electroconvulsive therapy and long-acting injectable aripiprazole for dopamine supersensitivity psychosis: a case report. Issue 3 (4th May 2022) - Matsuzaka, Yusuke; Noguchi, Manabu; Kanamura, Shigeki; Maeda, Kengo; Hisano, Takahiro; Tanaka, Daizo; Ando, Yukihiro; Yamamoto, Tomokazu; Morimoto, Yoshiro; Ozawa, Hiroki; Otsuka, Toshihiro
ABSTRACT: In the treatment of schizophrenia, long-term pharmacotherapy with D2-receptor antagonists can induce dopamine supersensitivity psychosis (DSP). We report a male patient with schizophrenia with suspected DSP due to excessive polypharmacy. He was hospitalized for several years. Most psychotropic drugs were reduced and subsequently stopped without the exacerbation of symptoms by administering modified electroconvulsive therapy (mECT). Aripiprazole was then selected as the main drug for treatment, which was subsequently changed to the long-acting injection formulation. He was eventually discharged and returned home. Combination therapy with mECT and aripiprazole, especially the long-acting injectable formulation, may help improve and prevent DSP.